Mechanism synthesis based on integration of dual quaternion motion polynomial decomposition and POC set and application of automotive multi-function door latch - QIN Pengcheng; HANG Lubin; LIU Zhe; CHEN Yong; HUANG Xiaobo; XIE Yuhang; ZHANG Ziyang (Jixie chuandong)
ObjectiveA mechanism synthesis method combining dual quaternion motion polynomial decomposition and POC set was proposed to meet the multi-function requirements of electric cinch, auxiliary opening and de-icing in the narrow space of automobile side door latch.MethodsBased on dual quaternions and using Bennett and RPRP mechanisms as sub-mechanisms, a 5R2P spatial mechanism motion polynomial was constructed. The RRPRPRR configuration was generated through polynomial factorization, and furthermore the RRPRRPR configuration was reconstructed based on the equivalence of POC set input-output equations of the connected parallel R and P axes in series.ResultsThe multi-mode RRPRRPR mechanism with variable degrees of freedom includes 2-DOF and 1-DOF motion modes, allowing for mode switching through transition configuration. Embedded within the automotive door latch and combined with mechanisms such as latch ratchet, locking pawl, limit block, and spring, the 5R2P mechanism achieves electric cinch, assisting opening, and de-icing functionalities. The 2-DOF mode of the 5R2P primarily accomplishes electric cinch and assisting opening, while the 1-DOF mode involves reciprocating motion impact between the end cam-type surface and the ratchet wheel-type surface, realizing de-icing for the automotive side door latch.